Um estudo enunciativo da palavra escravo e sua designação nas cartas do Conde do Pinhal para sua esposa Naninha - Dornas, Nayara Fernanda (2018)
Despite the difficulty of finding accurate data and documents regarding slavery in São Carlos, the slave was present throughout the development process of the city, but the slave is silenced throughout history. Thus, through an enunciative look provided by the theory of Semantics of the Event developed by the Brazilian scholar Eduardo Guimarães, the present work addresses the word slave and its designation throughout the letters of the Count of Pinhal to Anna Carolina, his wife, known as Naninha . We aim to study slave designations and also to identify slave designations in the relation with the proper name, adopting, in this way, the perspective that the event is the functioning of the language. We will use some resources of the theoretical-methodological contribution of Semantics of the Event as enunciative space, enunciative scene, enunciative agency, temporality, political, designation, articulation, rewriting and DSD developed by Guimarães, enunciative pertinence, domain of reference, force of progression, force of retrospection by Dias, and argumentation and presupposition by Ducrot. We intend, therefore, to study the designation of slave, silenced in this enunciative space and observe this silencing through the difficulty of finding accurate data and documents regarding slavery in São Carlos, and this is due to the determination of 1890 that ordered the incineration of documents which proved the property of the slave. That is, this measure is one of several attempts to silence and prevent the slave and his senses and meaning from gaining space. We also analyze the functioning of the proper names in the present of the enunciative event of the letters. We thus note that the proper names refer to the word slave, since the proper names are determined by the type of work developed, sometimes by the color of the skin, sometimes by the functioning of the name in other enunciations that through the relation of integration reveals the meaning of slave, so we have that proper names work with the sense of slaves.